Gender differences in outcomes after left atrial appendage closure with Watchman FLX device: insights from the Italian-FLX registry - Bonanni, Michela; Frazzetto, Marco; Nardone, Annalisa; Meucci, Francesco; Musto, Carmine; Quaranta, Gaetano; Saccà, Salvatore; Bedogni, Francesco; Maffeo, Diego; Ugo, Fabrizio; Guarracini, Fabrizio; Bocuzzi, Giacomo; et al. (Frontiers in Cardiovascular Medicine, 2024)
Introduction Recent studies have shown gender differences in cardiovascular outcomes after left atrial appendage closure (LAAC), highlighting different complication rates and adverse events, particularly in short-term assessments. As a result, there remains a significant knowledge gap on how these differences directly impact the efficacy and safety of LAAC procedures. The aim of this retrospective study was to investigate the clinical outcomes of LAAC in women and men using the Watchman FLX device. Methods This retrospective, multicenter study analyzes gender-specific outcomes in 650 patients who underwent LAAC with the Watchman FLX device between March 2019 and May 2022, drawn from the ITALIAN-FLX registry. Results The results show comparable rates of all-cause mortality, stroke, transient ischemic attack and major bleeding in men and women 12 months after the procedure. Notably, no significant gender differences were found for periprocedural complications. Conclusion In conclusion, this study shows that LAAC with the Watchman FLX device has comparable clinical outcomes between genders at both short-term and long-term follow-up.